Rekonstruksi Konsep Tas’īr Sebagai Instrumen Pengendalian Inflasi Beras Daerah: Studi Kabupaten Lampung Tengah dalam Perspektif Maqāṣid Syarī‘Ah - Linda Jayanti (CV. Creative Tugu Pena, 2026)
Tas’īr in Islamic economics is generally still discussed at the normative level regarding the permissibility of price fixing, while its relationship with regional inflation dynamics based on empirical data remains limited. Therefore, this study aims to analyze rice price fluctuations in Central Lampung Regency in 2025 and reconstruct the concept of tas’īr as an instrument for regional inflation control from the perspective of maqāṣid sharī‘ah. The case of Central Lampung is important to examine because it is an agrarian region and a rice production center, yet it still experienced rice price volatility during certain periods. This study employs a qualitative method with a normative-empirical approach based on document analysis. The primary data consist of the 2025 Price Development Index (Indeks Perkembangan Harga/IPH), policy reports of the Regional Inflation Control Team (Tim Pengendalian Inflasi Daerah/TPID), and Islamic economics literature. The findings reveal that rice price dynamics occurred in three phases: a stable phase from January to June, a rising phase with inflation peaking in September, and a correction phase in October. Price fluctuations were influenced by natural factors such as weather conditions, irrigation issues, and seasonal demand increases, as well as governance-related factors including inefficient distribution systems and long supply chains. In this context, tas’īr is no longer understood merely as direct price fixing, but rather as a corrective instrument of the state when market distortions occur, through strengthening supply, conducting market operations, maintaining food reserves, supervising distribution, and ensuring transparency of price information. This study emphasizes that the contemporary development of the concept of tas’īr can serve as a foundation for regional inflation control policies that are more just, adaptive, and oriented toward public welfare (maṣlaḥah).